A Decision Making Method for the Quality Identification of Wines Based on Fuzzy Soft Sets - Yong-Wei Yang (Fuzzy Information and Engineering, 2014)
Quality identification of wines is a crucial one for wine industry. The paper aims to give a decision making approach based on soft fuzzy sets for it. First, based on fuzzy soft sets, calculation steps are given to solve decision making problems. The grey relative coefficient between each alternative with the ideal alternative is calculated by grey relational analysis (GRA). Then, a relative relational degree is defined to determine ranking orders of all alternatives. Finally, an application of our proposed approach demonstrates its practicality and effectiveness in the quality identification of red wines.